2004
DOI: 10.1111/j.1440-1703.2004.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental determinants of the altitudinal variations in relative group densities of Japanese macaques on Yakushima

Abstract: Altitudinal variations in relative group densities of the Japanese macaques on Yakushima were studied. This is an ideal place for studying resource limitations because it avoids various complicating factors that are difficult to quantify but might affect animal densities, such as predation, interspecific competition, and past catastrophes. The relative group density was high in the coastal forest (0-400 m), while it did not differ among the higher zones (400-800, 800-1200 and 1200-1886 m). To examine this vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 39 publications
(52 reference statements)
2
56
1
1
Order By: Relevance
“…For example, Hanya et al (2004) examined the effects of both total annual fruit production and the degree of seasonality in fruiting (number of months when no fruit is available) on the density of a Japanese macaque (Macaca fuscata) population in Yakushima. They indicated that total annual fruit production affected density more than seasonality.…”
Section: Previous Studies On Primate Abundancementioning
confidence: 99%
“…For example, Hanya et al (2004) examined the effects of both total annual fruit production and the degree of seasonality in fruiting (number of months when no fruit is available) on the density of a Japanese macaque (Macaca fuscata) population in Yakushima. They indicated that total annual fruit production affected density more than seasonality.…”
Section: Previous Studies On Primate Abundancementioning
confidence: 99%
“…A second geographical component which is more poorly understood is the relationship between population density and elevation gradient. At present, it is not clear whether a density-elevation gradient relationship exists within a single species, since only one study is known to have investigated such an effect (Hanya et al 2004). …”
Section: Introductionmentioning
confidence: 97%
“…As a result, both the population and group density of macaques is about three times higher in the coastal forest (Hanya et al 2004). As a consequence, there are within and between-group contests for limited food in coastal forests (van Schaik 1989).…”
Section: Rhesusmentioning
confidence: 99%